The Effects of Populism on Liberal Democracy - Lindström,Kajsa (2021)
Recently there has been a rise of populism within Venezuela and Poland. Simultaneously, both countries have seen a de-democratization as a result of legal and political changes carried out by their governments. This study consists of a comparative analysis of two case studies on left-wing populism in Venezuela and right-wing populism in Poland, and aims at investigating the relationship populism and liberal democracy. I analyze these cases using the theories presented by Nadia Urbinati in her work Democracy Disfigured (2014). The results show that despite the different types of populism, both parties have in similar ways contributed to the de-democratization in their countries. I provide three hypotheses on how this has happened; (1) because it leads to a centralization of powers by mobilizing the majority to violate the checks and balances and the separation of powers; (2) because the anti-pluralistic nature of populism can legitimize a tyrannic majority rule, that is able to evade and disregard the rights of minorities and oppositions; (3) because it can undermine the legitimacy and interfere in the work of independent institutions outside of the government.
Keywords: Venezuela; Poland; Populism; Liberal Democracy; De-democratization; Chávez; Law and Justice.